Reclaiming place An eco-theological response to the 'miasma of temporocentrism' - Guess, Deborah (2017)
In contrast to the way that Christian and Western thought have tended to prioritize time and history over place and geography, an ecological sensibility requires a counter-balancing geographical emphasis. Using a contemporary definition of place as a meeting between the global and the local, two eco-theological claims can be made: that the tradition is more strongly rooted in place than has always been acknowledged; and the idea that, through the event of the Incarnation, place can be seen as reconstituted yet concretized. This means that the previously neglected category of place achieves greater significance in relation both to the life and ministry of Jesus Christ and implicitly to the lives of all Christians at all times and places. This focus on place contributes to a theology which is amenable to the radical challenges of today's ecological context.
Keywords: Incarnation; Eco-theology; Ecology; Geography; Place; temporocentrism